Simulation of temperature compensated waveguiding layer acoustic wave devices. (13th December 2018) - Shen, Junyao; Fu, Sulei; Li, Qi; Song, Cheng; Zeng, Fei; Pan, Feng
Abstract: Packageless structure which can reduce dimension has been a hot spot of research, while devices with temperature stability have received great attention. The temperature compensated waveguiding layer acoustic wave (WLAW) is a good candidate for devices with packageless structure and temperature stability. We propose an AlN/interdigital transducer (IDT)/ZnO/SiO2 /Si multi-layered structure and investigate the propagation characteristics of the wave by simulation. The influence of the AlN thickness on the wave confinement is discussed, while the phase velocity, electromechanical coupling factor ( K 2 ) and temperature coefficient of frequency (TCF) are provided as functions of the normalized ZnO and SiO2 thicknesses. The results show that a WLAW with nearly zero TCF can be obtained in the structure where the thickness of AlN is larger than 1.5 λ ( λ stands for the wavelength of the acoustic wave), that of ZnO is between 0.2 λ and 0.3 λ, while the thickness of SiO2 is about three times that of ZnO. In this multi-layered structure, we can obtain temperature compensated WLAW devices with different frequencies and K 2 . This work can provide instruction for experiments and is also useful for preparing devices with different velocities, K 2 and TCF based on this multi-layered structure.